Uncertain product risk, information acquisition, and product liability - Tim Friehe; Elisabeth Schulte (Philipps-University Marburg, School of Business and Economics, 2017)
We describe how product liability interacts with regulatory product approval in influencing a firm's incentives to acquire information about product risk, using a very parsimonious model. The firm may have insufficient information acquisition incentives when it is not fully liable for the harm caused by its product. The firm may also have excessive information acquisition incentives under both full and limited liability. We highlight efficiency inducing liability rules.
Keywords: K13; O31; D83; 330; Innovation; Product Liability; Uncertainty